2006
DOI: 10.1212/01.wnl.0000233916.57415.9d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on levodopa pharmacokinetics and pharmacodynamics in Parkinson disease

Abstract: The authors studied the acute effect of caffeine on the levodopa pharmacokinetics and pharmacodynamics in 12 patients with idiopathic Parkinson disease. This double-blind, randomized, crossover study revealed that caffeine shortened the maximal plasma concentration of levodopa, decreased the latency to levodopa walking and tapping motor response, and increased the magnitude of walking response. Caffeine administered before levodopa may improve its pharmacokinetics in some parkinsonian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
0
22
0
3
Order By: Relevance
“…25,26 Numerous animal studies have found motor improvement in toxin-induced models of PD, 27 in dopamine-deficient mice, 28 and in drug-induced parkinsonism 29 with caffeine. Caffeine may also increase bioavailability and prolong the clinical effect of levodopa 30 (note that the clinical effect of caffeine may persist even after levodopa levels decline, suggesting that the D2 receptor interactions are also important). Two early smallscale human studies evaluated caffeine as a potential symptomatic agent in PD, and found no effect.…”
Section: Caffeine and Edsmentioning
confidence: 99%
“…25,26 Numerous animal studies have found motor improvement in toxin-induced models of PD, 27 in dopamine-deficient mice, 28 and in drug-induced parkinsonism 29 with caffeine. Caffeine may also increase bioavailability and prolong the clinical effect of levodopa 30 (note that the clinical effect of caffeine may persist even after levodopa levels decline, suggesting that the D2 receptor interactions are also important). Two early smallscale human studies evaluated caffeine as a potential symptomatic agent in PD, and found no effect.…”
Section: Caffeine and Edsmentioning
confidence: 99%
“…Moreover, the beneficial effects of caffeine in Parkinson's disease patients was also reported [66]. Furthermore, caffeine administered before levodopa may improve its pharmacokinetics in some patients with Parkinson's disease [67].…”
Section: Parkinson's Diseasementioning
confidence: 89%
“…Caffeine may shorten the time to maximum concentration and increase the magnitude of the response. 253 To tailor therapy to an individual patient, the clinician should be aware of the magnitude and duration of the motor response after a dose of levodopa/ carbidopa, and the relationship between "on" and "off " periods and dyskinesias. This can sometimes be determined from the patient history but occasionally may require monitoring of the patient during several dosing cycles.…”
Section: 242mentioning
confidence: 99%